Association Between Obstructive Sleep Apnea and Hearing Loss Using 2019-2021 Korea National Health and Nutrition Examination Survey Data - Ahn, Jungmin; Hong, Seung-Eun; Kim, Brian; Lee, Byeong-Cheol; Lee, Myung-Chul; Choi, Ik Joon (Journal of International Advanced Otology, 2025)
Background: The association of hearing loss with obstructive sleep apnea (OSA) has been investigated in several studies, but analyses using large national population-based datasets are lacking. Therefore, we aimed to determine the effect of the severity of OSA on hearing loss using data from the Korea National Health and Nutrition Examination Survey (KNHANES). Methods: We reviewed the KNHANES data from 2019 to 2021, analyzing 7730 subjects aged 40 and older who completed the sleep health survey (STOP-BANG questionnaire, SBQ) and hearing assessment. According to their SBQ scores, subjects were classified into low-, intermediate-, and high-risk OSA groups. Hearing loss was defined as a pure-tone average (PTA) greater than 25 dB at frequencies of 0.5, 1, 2, and 4 kHz in the better ear. In addition, low- and high-frequency hearing loss was defined as PTA >25 dB at 0.5, 1, and 2 kHz and PTA >40 dB at 2, 4, and 8 kHz, respectively. Results: Of a total of 7730 subjects, 4781 (62.4%), 2534 (31.7%), and 415 (5.9%) belonged to the low-, intermediate-, and high-risk groups, respectively. Mean hearing thresholds were significantly higher in the intermediate-, high-, and intermediate/high-risk groups compared to the low-risk group (all P < .001). After adjusting for related variables, logistic regression analyses revealed that hearing loss was not significantly correlated with OSA severity in the male subgroup. However, female subjects with more than an intermediate risk of OSA had a 1.372 times higher risk of hearing loss than those with a low risk of OSA (odds ratio: 1.372, 95% CI: 1.039-1.814). Conclusion: The study found that the risk of hearing loss was significantly related to the severity of OSA in the female subgroup. Cite this article as: Ahn J, Hong S, Kim B, Lee B, Lee M, Choi IJ. Association between obstructive sleep apnea and hearing loss using 2019-2021 Korea national health and nutrition examination survey data. J Int Adv Otol. 2025, 21, 1356, doi: 10.5152/iao.2025.231356